Effects of Steel Slag Usage as Aggregate on Indirect Tensile and Creep Modulus of Hot Mix Asphalt - Kok, Baha Vural; Kuloglu, Necati (Gazi Univ, 2008)
In this study indirect tensile modulus and long term deformation behaviour of the hot mix asphalt (HMA) containing steel slag, basalt and limestone were investigated using 5 pulses Universal Testing Machine. Optimum bitumen content was determined for three types of mixtures according to the Marshall procedure. Indirect tensile modulus ITM (Sm) and creep modulus (S) tests were applied in order to investigate the effects of the steel slag usage on the pavement. To investigate the effects of air void on indirect tensile and creep modulus of mixtures, the mixtures prepared were also subjected to different numbers of compaction blows between 35 and 75 at optimum bitumen content to maintain different air void content. The steel slag mixes were compared with basalt and limestone mixes. The highest Sm values were obtained with steel slag mixes. In terms of creep modulus the basalt mixes were found to have higher values than the others. However the steel slag mixes provide a remarkable value as basalt mixes. This study also indicates that a certain correlation exists between air voids and indirect tensile and creep modulus, and provide to compare these properties according to air void contents.
Keywords: Steel slag; Hot mix asphalt; Indirect tensile modulus; Creep modulus